The Existence Of Pedicab In Developing Tourism In Malioboro - Santoso, Ihsan Budi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2018)
The objective of this research is to describe â€œthe existence of pedicab in developing tourism in Malioboroâ€ which is viewed from the perception of pedicab drivers toward tourism in Malioboro and the strength and the obstacle of a pedicab. Malioboro is one of the tourist objects in the City of Yogyakarta that currently still to place the public transportation non motorized such as pedicab in developing the tourism in Malioboro. Its existence is also one of the tourism activities in the region that have made as to the beautiful one for tourists. This research is descriptive qualitative. The data is collected through observation, an interview and a literature review. The result of the research shows that the perception of pedicab drivers toward its tourism is good. There is progress in tourism in Malioboro street. Second, it can be viewed from the strengths and the obstacles of pedicabs. The strength shows that pedicab is a means of promotion and advertisement of tourism in Malioboro. The pedicab is an icon of Yogyakarta, especially in Malioboro. The obstacle is the existence of competitors in the field. This condition makes the difficulties for the pedicab as non-motorized transportation. In the economic aspect, this phenomenon will influence the economic life of the pedicab driver.